FOSTERING LEARNING AUTONOMY AND CREATIVITY IN CROSS CULTURAL UNDERSTANDING THROUGH PROJECT-BASED LEARNING - Istikharoh, Lutfi; Nurhayati, Sulasih (University of Kuningan, 2023)
Teachers require instructional resources to assist students in learning. This research met the material requirements of students and evaluated 21st-century learning and the analysis of popular literary works in various countries. Thirty students in English Education and Literature participated in this study. The research was primarily concerned with three topics: design of Booklet Journey to the World, the 21st century skills in project-based learning, and literary work analysis as one of the booklet's sections. Three instruments were used to gather data from the field. Document analysis, a Focused-Group Discussion (FGD) interview, and a questionnaire indicate students' perspectives of their writing process through the implementation of project-based learning. Three points disclosed: 1) The booklet displayed good creativity, idea courage, and language; 2). Concerning the compatibility of learning models and instructional materials, creativity; and self-directed learning, the three criteria were met by 53.34 percent, 63.34 percent, and 56.67 percent of respondents, respectively which means that the students' perception on the implementation of project-based learning was rated as excellent; 3) The majority of works included in the booklet were collected, paraphrased, and commented on, demonstrating sufficient, effective, and thorough literary comprehension.